Kedudukan Barang Bukti Yang Diperoleh Secara Melawan Hukum Dalam Putusan Mahkamah Agung Nomor 1614 K/ Pid.Sus /2012 - A. Zainur Rasyidi Ramadhani (Faculty of Law, Universitas Airlangga, 2024)
Abstract National Police of the Republic of Indonesia is a institution that has functions to provide protection to the society. For the implementation of enforcement law, investigator conducts inquiry and investigation as the first step of the whole law enforcement process. Unfortunately, police officers often obtain unlawful evidence during the investigation process in order to frame a suspect. Admissibility of Evidence is invalid. This situation make no chance for the framed suspect to fight for the rights. Indonesian criminal procedure law establishes